AD, Volume 21, n° 1, 1996 - Full Issue - Journal System (Africa Development, 1996)
Contents / Sommaire Diagnostic du système éducatif béninois: Eléments pour une réforme novatrice des systèmes éducatifs africains Dénis Amoussou-Yeye ................... 5 The Structural Adjustment Programme and the Transition to Civil Rule in Nigeria (1986-1993) Abubakar Momoh .........................19 A Preliminary Study of the Socio-Economic Impact of HIV/AIDS in Africa Theresa M. Ndongko ................... 39 Le secteur informel une réalité à réexplorer: ses rapports avec les institutions et ses capacités développantes Abdoulaye Niang ........................... 57 The Electricity Supply Industry in Ghana: Issues and Priorities Abeeku Brew-Hammond ................ 81 Analysis of Commercial Bank Lendings to African Countries Odedokun Μ.Ο ................................ 99 Book Reviews Pour un autre regard des mutations présentes du syndicalisme sénégalais Ousseyhou Faye ........................... 123 Kenyan Capitalists, The State and Development by David Himbara Peter Mwangi Kagwanja ................... 127 CIDA and Sustainable Development: How Canada's Aid Policies Can Support Sustainable Development in the Third World More effectively by Jim MacNeill Leonardo Ngabo Lutaaya ...................... 131 Publications Received and Acquired ................ 135 Index to Africa Development Vol. XX, 1995 ..............137